2021
DOI: 10.3389/fcvm.2021.702586
|View full text |Cite
|
Sign up to set email alerts
|

Circle the Cardiac Remodeling With circRNAs

Abstract: Cardiac remodeling occurs after the heart is exposed to stress, which is manifested by pathological processes such as cardiomyocyte hypertrophy and apoptosis, dendritic cells activation and cytokine secretion, proliferation and activation of fibroblasts, and finally leads to heart failure. Circular RNAs (circRNAs) are recently recognized as a specific type of non-coding RNAs that are expressed in different species, in different stages of development, and in different pathological conditions. Growing evidences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…CircSLC8A1, which is enriched in cardiomyocytes, was reported as the most abundant circRNA in the human heart 58 . CircRNAs are also implicated as potential candidates for the treatment of cardiac fibrosis 27,59,60 . A recent study reported 662 circRNA-miRNA-mRNA interactions in heart failure patients 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircSLC8A1, which is enriched in cardiomyocytes, was reported as the most abundant circRNA in the human heart 58 . CircRNAs are also implicated as potential candidates for the treatment of cardiac fibrosis 27,59,60 . A recent study reported 662 circRNA-miRNA-mRNA interactions in heart failure patients 61 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have been shown to regulate angiogenesis and EC response to ischemia/reperfusion (I/R) injury 26,27,28 . We have recently reviewed the RNA regulatory role of circRNAs in IHD and cardiac remodelling 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…As a non-coding RNA, circRNA was recently discovered. Previous studies have reported that circRNAs are associated with vascular dysfunction and multiple processes, such as vascular development, growth and remodelling ( 42 - 48 ). The present study performed a high-throughput transcriptome sequencing analysis of the PASMCs to investigate the differently expressed circRNAs and finally identified the upregulated circ-Grm1.…”
Section: Discussionmentioning
confidence: 99%
“…It can participate in protein translation. 36 CirRNAs are widespread and diverse in eukaryotic cells, 37 but relatively stable in the cytoplasm. 38 CirRNAs can be co-transcribed and post-transcribed by a process of reverse splicing or head-tail circular splicing, in which the downstream exon splices in reverse order to the upstream exon.…”
Section: Epigenetic Regulatory Mechanismsmentioning
confidence: 99%